Positive solutions of Volterra integral equations using integral inequalities. Issue 2 (2002) - Meehan, Maria; O'regan, Donal
Abstract : The existence of positive solutions of certain special cases of the possibly singular Volterra integral equationy ( t ) = ∫ 0 t k ( t, s ) [ f ( y ( s ) ) + g ( y ( s ) ) ] d s,     t ∈ [ 0, T ] is discussed, using Krasnoselskii's fixed point theorem.